2004
DOI: 10.1002/jsfa.1973
|View full text |Cite
|
Sign up to set email alerts
|

Variations in cadmium accumulation among rice cultivars and types and the selection of cultivars for reducing cadmium in the diet

Abstract: A pot trial was conducted with 52 rice cultivars of different types collected from different origins. The results showed that there were great differences in Cd concentrations in straw, brown rice and grain chaff among the rice cultivars grown in a soil containing a Cd concentration of 100 mg kg −1 ; the Cd concentrations in brown rice ranged from 0.22 to 2.86 mg kg −1 . The great genotypic differences in Cd concentrations indicated that it is possible to lower the Cd content of rice through cultivar selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
77
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 168 publications
(95 citation statements)
references
References 27 publications
5
77
0
4
Order By: Relevance
“…Different plant processes such as respiration, photosynthesis, water and nutrient uptake of plants are badly affected by Cd (Kuo and Kao, 2004). Cadmium reduces root growth because of the reduction of the rate of new cell production (Liu et al, 2004), inhibits the activities of antioxidative enzymes of plants (Correa et al, 2006) and induces oxidative stress in cells (Sandalio et al, 2001). Nickel (Ni) is an important toxic heavy metal, and pollution by Ni has gained importance due to the greater understanding of its persistence and toxicity in the ecosystems (Alemayehu and Lennartz, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Different plant processes such as respiration, photosynthesis, water and nutrient uptake of plants are badly affected by Cd (Kuo and Kao, 2004). Cadmium reduces root growth because of the reduction of the rate of new cell production (Liu et al, 2004), inhibits the activities of antioxidative enzymes of plants (Correa et al, 2006) and induces oxidative stress in cells (Sandalio et al, 2001). Nickel (Ni) is an important toxic heavy metal, and pollution by Ni has gained importance due to the greater understanding of its persistence and toxicity in the ecosystems (Alemayehu and Lennartz, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the variety screening trial demonstrated that the element uptake and accumulation capacities varied in different rice varieties, just like the results of Morishita et al (1987), Liu J. G. et al (2005, and Norton et al (2009). Among the 15 rice varieties tested, the highest K, Ca, and Mg contents appeared in the grains of P1; however, its As content exceeded the NFHSC, whereas the Cd content did not.…”
Section: Discussionmentioning
confidence: 61%
“…The differences observed in accumulation may be related to the genotypic tolerance nature of the cultivars to cadmium toxicity. Genotypic variations of Cd tolerance in rice cultivars were reported by Liu et al (2005). Cadmium uptake and translocation from contaminated soil to plants edible parts were markedly different among plant species as well as cultivars within the same species (Liu et al 2007).…”
Section: Discussionmentioning
confidence: 99%